2007
DOI: 10.1111/j.1532-950x.2007.00246.x
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Comparison of Dual Interlocking Single Loop and Double Loop Tension Band Techniques to the Classic AO Tension Band Technique for Repair of Olecranon Osteotomies in Dogs

Abstract: The DL construct is easy to perform, less bulky, and provides comparable fragment stability to standard TBW techniques at functional loads. Surgical method is important for optimal performance of all TBW constructs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 26 publications
1
19
0
Order By: Relevance
“…The failure load was highly correlated with and scaled with the initial tension by a factor of 2.3, so creating more tension in a TB construct during tying means that it will resist greater loads before it begins to loosen. Our results are in line with previous studies in which the double loop generated greater static tension and a higher yield load and resisted higher loads at 2 mm of displacement compared with single loop or twist constructs. In the study reported here, the figure‐of‐eight TB construct with two twists resisted distraction of the trochanter fragment better than the one with one twist and thus was able to achieve a 21% higher force before failure at 2 mm (199 vs 165 N).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The failure load was highly correlated with and scaled with the initial tension by a factor of 2.3, so creating more tension in a TB construct during tying means that it will resist greater loads before it begins to loosen. Our results are in line with previous studies in which the double loop generated greater static tension and a higher yield load and resisted higher loads at 2 mm of displacement compared with single loop or twist constructs. In the study reported here, the figure‐of‐eight TB construct with two twists resisted distraction of the trochanter fragment better than the one with one twist and thus was able to achieve a 21% higher force before failure at 2 mm (199 vs 165 N).…”
Section: Discussionsupporting
confidence: 92%
“…Because the knot or fold is the weak point of the system, more force is required to unbend two arms (DL) than to untwist two wires wrapped around each other, as is present in the other three constructs. We found the following factors important for producing the most secure construct and maximizing TB performance: (1) forming small loops to reduce the impact of loop elongation under load (DL, DISL), (2) pressing the wire flat to the trochanter fragment and minimizing laxity as it is looped around, and (3) maintaining wire tension throughout tying by applying continual pressure on wire tightener cranks while bending over the wire for DL or pulling up during the twist‐and‐lay technique for OT and TT.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations